LongR3 enhances Fc-fusion protein N-linked glycosylation while improving protein productivity in an industrial CHO cell line. (February 2017) - Qian, Yueming; Lewis, Amanda M.; Sidnam, Sarah M.; Bergeron, Alison; Abu-Absi, Nicholas R.; Vaidyanathan, Nisha; Deresienski, Adam; Qian, Nan-Xin; Borys, Michael C.; Li, Zheng Jian
Graphical abstract: Highlights: Insulin-like growth factor analog LongR3 increases sialic acid content of Fc-fusion protein. LongR3 down-regulates sialidase gene expression. Decreased extracellular sialidase prevents recombinant glycoprotein desialylation. Abstract: Glycosylation is a critical quality attribute for many therapeutic glycoproteins. Numerous studies in academia and industry have sought to understand and control protein glycosylation in order to obtain consistent glycoform profiles in production. In many cases, the resulting enhancement of protein glycosylation comes at the expense of protein productivity. Here we examine the impact of insulin-like growth factor-I analogue, LongR 3 (LR3), on an Fc-fusion producing Chinese Hamster Ovary (CHO) cell process. We observe that LR3 improves protein productivity and significantly increases protein N-linked glycosylation. The beneficial effects can be seen at low concentrations (micrograms/L), which allows LR3 to be a cost-efficient additive for improving cell culture performances. The recombinant protein examined in this study has both higher sialic acid content and lower percent of asialylated species of N-linked glycans in the presence of LR3. Finally, CHO-specific glycosylation Real-Time Reverse Transcription (RT 2 ) PCR Arrays combined with an enzymatic assay demonstrate that LR3 significantly down-regulates cytosolic sialidase gene Neu2 and hexosaminidase-D gene Hexdc, decreases extracellular sialidase activity, and therefore prevents recombinant glycoprotein desialylation.